Synthesis of Some Novel Pyrazolopyridooxazine, Pyrazoloquinolizines, Pyrazoloindolizine and Pyrazolopyranopyrimidinone Derivatives - H. Al-Tilasi, Hissah; E.M. El-Baih, Fatma (Asian Journal of Chemistry, 2014)
Different pyrazolone derivatives were prepared as starting materials for the synthesis of pyrazolopyridooxazine, pyrazoloquinolizines, pyrazoloindolizine, 1,4-oxazinopyrazolines and pyrazolopyranopyrimidinone derivatives via reactions with different reagents applying the one pot multicomponent reaction using microwave and ultrasound irradiation in some cases.